2016
DOI: 10.1371/journal.pone.0151630
|View full text |Cite
|
Sign up to set email alerts
|

Daughters at Risk of Female Genital Mutilation: Examining the Determinants of Mothers’ Intentions to Allow Their Daughters to Undergo Female Genital Mutilation

Abstract: Female genital mutilation (FGM) is still a common practice in many countries in Africa and the Middle East. Understanding the determinants of FGM can lead to more active interventions to prevent this harmful practice. The goal of this study is to explore factors associated with FGM behavior among Iranian mothers and their daughters. Based on Ajzen’s theory of planned behavior, we examined the predictive value of attitudes, subjective norms, perceived behavioral control and several socio-demographic variables i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 41 publications
(63 reference statements)
5
33
0
Order By: Relevance
“…The logistic regression analysis showed that knowledge, attitude, religion and women’s status are significant predictors of future FGM practice among the daughters of females, with attitude that FGM is a good practice representing the major cause. These findings were in agreement with Pashaei et al who examined the determinants of women’s intentions to subject their daughters to FGM, and it was found that attitude was the strongest predictor of perpetuation of FGM [ 18 ]. Therefore, intervention programs to decrease FGM might focus primarily on converting women’s positive attitude toward FGM into negative attitude, and on alleviating the perceived social pressure to mutilate one’s daughter [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…The logistic regression analysis showed that knowledge, attitude, religion and women’s status are significant predictors of future FGM practice among the daughters of females, with attitude that FGM is a good practice representing the major cause. These findings were in agreement with Pashaei et al who examined the determinants of women’s intentions to subject their daughters to FGM, and it was found that attitude was the strongest predictor of perpetuation of FGM [ 18 ]. Therefore, intervention programs to decrease FGM might focus primarily on converting women’s positive attitude toward FGM into negative attitude, and on alleviating the perceived social pressure to mutilate one’s daughter [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…Although our analysis reveals that women who supported the practice were more likely to be circumcised, it is noteworthy that the majority of the women who have undergone FGM/C are in support of the practice. Being circumcised may not necessarily mean being supportive of the practice [ 36 ]. Parents and family or the duress of social and peer pressure initiated the decision for circumcision in most cases [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Being circumcised may not necessarily mean being supportive of the practice [ 36 ]. Parents and family or the duress of social and peer pressure initiated the decision for circumcision in most cases [ 36 , 37 ]. As most of the young women in the present study had been circumcised prior to migration, it is apparent that most of them were circumcised at an early age based on parental/family decision, as circumcision is a common practice between the ages of 6 and 8 years in Somalia [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a comprehensive search, we could not find evidence assessing the effectiveness of CBT for PTSD, depression, or anxiety disorders in girls and women living with FGM. It appears that the majority of primary studies have focused on investigating the prevalence of the practice among different cultures, the physical and psychological complications associated with it, as well as the factors promoting this harmful procedure . Additional research on how to provide better psychological care for this population remains an important priority.…”
Section: Discussionmentioning
confidence: 99%